2015
DOI: 10.1371/journal.pone.0136932
|View full text |Cite
|
Sign up to set email alerts
|

Network Modeling Reveals Cross Talk of MAP Kinases during Adaptation to Caspofungin Stress in Aspergillus fumigatus

Abstract: Mitogen activated protein kinases (MAPKs) are highly conserved in eukaryotic organisms. In pathogenic fungi, their activities were assigned to different physiological functions including drug adaptation and resistance. Aspergillus fumigatus is a human pathogenic fungus, which causes life-threatening invasive infections. Therapeutic options against invasive mycoses are still limited. One of the clinically used drugs is caspofungin, which specifically targets the fungal cell wall biosynthesis. A systems biology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 50 publications
4
68
0
Order By: Relevance
“…Both Δ atfA Afs35 and Δ atfA CEA17 had decreased growth in 1.2 M sorbitol (Figure a), while Δ atfB‐D CEA17 showed comparable growth with the wild‐type strain (data not shown). Alterations in osmolarity can have an impact on the composition and structure of the cell wall (Valiante et al, ; Altwasser et al, ; Winkelströter et al, a; Bom et al, ; Bruder Nascimento et al, ). In accordance, both Δ atfA Afs35 and Δ atfA CEA17 mutants were sensitive to the cell wall‐damaging agents calcofluor white and Congo red.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both Δ atfA Afs35 and Δ atfA CEA17 had decreased growth in 1.2 M sorbitol (Figure a), while Δ atfB‐D CEA17 showed comparable growth with the wild‐type strain (data not shown). Alterations in osmolarity can have an impact on the composition and structure of the cell wall (Valiante et al, ; Altwasser et al, ; Winkelströter et al, a; Bom et al, ; Bruder Nascimento et al, ). In accordance, both Δ atfA Afs35 and Δ atfA CEA17 mutants were sensitive to the cell wall‐damaging agents calcofluor white and Congo red.…”
Section: Resultsmentioning
confidence: 99%
“…Another interesting aspect was the upregulation upon osmotic stress of several genes encoding for protein kinases related to calcium and TOR, such as calcium calmodulin (CmkD showed only a discrete increase. It has been proposed that increased concentrations of caspofungin promoted activation and cross-talk between the A. fumigatus MpkA and SakA pathways (Altwasser et al, 2015;Bruder Nascimento et al, 2016;Valiante et al, 2015b). Additionally, the existence of a salvage pathway, possibly dependent on MpkC and SakA, which would compensate the caspofungin stress response, has been proposed (Valiante et al, 2015b).…”
Section: Atfa Is Important For a Fumigatus Virulence In Both Gallementioning
confidence: 99%
See 1 more Smart Citation
“…In A. fumigatus MpkC and SakA are paralogues of the S. cerevisiae Hog1, which is the main regulator of the HOG pathway (Maeda et al, 1994). SakA and MpkC play a role in carbon utilization and adaptations to the antifungal agent, caspofungin (Reyes et al, 2006;Altwasser et al, 2015;Valiante et al, 2015). Pascual-Ahuir and Proft (2007) have shown that Sch9 is involved in the regulation of adaptations to acute hyperosmotic stress in S. cerevisiae.…”
Section: Aspergillus Fumigatusmentioning
confidence: 99%
“…GCCN is similar to the widely used term cross-talk network but we make the distinction between the two as the following: GCCN only refers to gene level communications, whereas cross-talk network term is used to describe communication in any molecular levels between different cell-types. In summary, the defined GRCN and GCCN terms of this study are more specific than the well-established crosstalk networks (CTN) term that is widely used for any type of network that refers to communication between different cell types at any molecular level [10][11][12][13][14][15]. We consider that GRCN and GCCN are yet to be explored as a relatively new avenue of research and catch up with the classical gene networks inference research of single cell types.…”
Section: Gene Level Network Between Two Different Cell Typesmentioning
confidence: 99%